1972
DOI: 10.1104/pp.50.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-induced Stimulation of Acceptorless Respiration in Corn Mitochondria

Abstract: In a recent paper (11) we suggested that high state 4 respiration rates in corn mitochondria are linked to energy expenditure in phosphate transport. State 4 respiration was considerably augmented by polycations which served to increase phosphate transport, producing swelling. It seems to be widely accepted that energy-linked ion transport in mitochondria is a process capable of releasing coupled respiration (3,20,21), although it is sometimes pointed out that the stoichiometry is disturbing (3), and that perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…If the main driving forces, A I and ApH generated by electrogenic proton pumps (10) are used for K+ and Pi uptake, respectively, it should be possible to differentiate the energycoupling requirements for these two ions either by changing the proton gradient across the membrane or by chemically modifying the transport carrier. Accordingly, several chemical probes such as the ATPase stimulator, FC2 (18), the inhibitor, DES (2), the OH-/Pi antiporter inhibitor, mersalyl (8,16) 4 h, or more, are "stable" in their physiological activities (7,20), most of the experiments were conducted using washed tissues.…”
mentioning
confidence: 99%
“…If the main driving forces, A I and ApH generated by electrogenic proton pumps (10) are used for K+ and Pi uptake, respectively, it should be possible to differentiate the energycoupling requirements for these two ions either by changing the proton gradient across the membrane or by chemically modifying the transport carrier. Accordingly, several chemical probes such as the ATPase stimulator, FC2 (18), the inhibitor, DES (2), the OH-/Pi antiporter inhibitor, mersalyl (8,16) 4 h, or more, are "stable" in their physiological activities (7,20), most of the experiments were conducted using washed tissues.…”
mentioning
confidence: 99%
“…If the site of DNP inhibition is associated with the dissipation of I X, then it seems unlikely that the pumping of K+, which results in contraction, in a KCI medium is involved directly with I~X. Hanson et al (8) suggest this schematically where they show the outpumping of K+ to be associated with the proton motive force generated from respiration and not from the dissipation of I -X.…”
Section: Discussionmentioning
confidence: 99%
“…This transport is inhibited by mersalyl and can be followed via percentage transmittance changes (8). When comparative studies of the effects of mersalyl and kaempferol were conducted, kaempferol was found to have no effect on the transport of phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations